Reclaiming the women of Britain's first mission to West Africa : three lives lost and found - Leach, Fiona E. (Studies of Religion in Africa, 2018)
Reclaiming the Women of Britain's First Mission to Africa is the compelling story of three long-forgotten women, two white and one black, who lived, worked and died on the Church Missionary Society's first overseas mission at the dawn of the nineteenth century. It was a time of momentous historical events: the birth of Britain's missionary movement, the creation of its first African colony as a home for freed slaves, and abolition of the slave trade. Casting its long shadow over much of the women's story was the protracted war with Napoleon. Taking as its starting point a cache of fifty letters from the three women, the book counters the prevailing narrative that early missionary endeavour was a uniquely European and male affair, and reveals the presence of a surprising number of women, among them several with very forceful personalities. Those who are interested in women's life history, black history, the history of the slave trade and British evangelism will find this book immensely enjoyable.